ANALISIS YURIDIS DASAR PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN TERHADAP PELAKU TINDAK PIDANA PEMALSUAN SURAT BERDASARKAN PASAL 263 KUHP (Putusan 876/Pid.B/2019/PN Rap ) - Muhammad Rafi’i Abdillah (Jurnal Ilmiah Advokasi, 2020)
Falsification of signatures or stamps / stamps is one of the forms of letter forgery and the use of fake letters in question is someone who deliberately uses a letter that he knows is fake. Using a forged or falsified letter is one of the criminal acts regulated in Chapter XII Book II Article 263 paragraph 2 of the Criminal Code (KUHP). Formulation of Article 263 of the Criminal Code.The approach method used in this study is a normative method supported by empirical methods. In this article, it is emphasized that in its use, you must really know that the letter used is fake and can cause harm. With the existence of legal provisions regulating these crimes, according to the function of the law as a means of social control and punishment as a repressive effort to tackle crimes.Keywords: Letter forgery, Judge's Consideration, Article 263 of the Criminal Code